Fatalism reconceptualized: A concept to predict health screening behavior - STRAUGHAN, Paulin Tay (Institutional Knowledge at Singapore Management University, 1998)
Social norms governing health seeking behavior affect perceived self-efficacy which in turn determines if self-directed change is sustained. Using this argument, we contextualized the link between social background and preventive health behavior. We argued that fatalism influenced self-efficacy, which in turn affected acceptability of four screen tests: mammography, clinical breast examination, breast self-examination, and the Pap Smear Test. A seven-item index was developed to measure fatalism. From data obtained through a community survey of women between 50 to 65 years, the index was validated. Logistic regression was conducted to verify the empirical link between fatalism and the four screen tests. A multivariate model that explained variation in fatalism was derived and the results showed that emotional support from family and friends, informational support from personal physicians, as well as social background factors (education, ethnicity, income, and age) were significantly correlated to fatalism. By improving our understanding of the social obstacles that deter women from adopting regular screening, more effective intervention can be employed to improve acceptability of these screen tests.